THE POTENTIAL OF FRAGRANT PANDAN LEAVES AS ACTIVE INGREDIENTS IN COSMETIC PRODUCTS: PHYTOCHEMICAL ANALYSIS - Nurbaiti, Siwi; Bella Triyanti, Sinta; Herayati, Herayati (Indonesian Journal of Cosmetics, 2025)
This study aimed to evaluate the phytochemical composition of Pandanus amaryllifolius (fragrant pandan) leaf extract as a preliminary assessment of its potential application in herbal cosmetic formulations. The extraction was performed using the maceration method with 95% ethanol as the solvent. Qualitative phytochemical screening was conducted to identify major classes of secondary metabolites. The results confirmed the presence of alkaloids, flavonoids, tannins, polyphenols, and saponins, while steroids and triterpenoids were not detected. Each identified compound group is known to contribute important biological activities, including antioxidant, anti-inflammatory, and antimicrobial effects, which are desirable in topical skincare products. These findings provide foundational evidence that P. amaryllifolius leaves are a promising natural source of multifunctional bioactive compounds for future cosmeceutical development.